Enseñanza de la resolución de triángulos aplicados al Fashion Design para grado décimo (2021)
In this work you will find didactic material designed for the teaching and learning of trigonometry in tenth grade. Here we work on the resolution of triangles through the different theorems: Pythagoras, trigonometric ratios, sine and cosine law, all applied to Fashion Design. The methodological basis of this work focuses on learning meaningful and project-based learning, always trying to strengthen metric thinking, measurement system and the process of formulating, comparing and exercising procedures. This will be evident in each guide, as students will have to design clothing using different patterns and the knowledge acquired in solving triangles.